Nested Explorative Maps: A new 3D canvas for conceptual design in architecture. (August 2019) - Olivier, Pauline; Chabrier, Renaud; Rohmer, Damien; de Thoisy, Eric; Cani, Marie-Paule
Highlights: A recursive solution for creating a 3D sketch by drawing on semi-tranparent surfaces, themselves extruded from 2D footprints. A system composed of a sketching interface with the associated vizualisation and editing tools for a real-time interaction. A method based on local attractions to dense stroke regions to enable interactive navigation through the alternative designs. This navigation drive displacements plus free-form deformation of the nested construction surfaces carrying the user strokes. Graphical abstract: Abstract: In this digital age, architects still need to alternate between paper sketches and 3D modeling software for their designs. Indeed, while 3D models enable to explore different views, creating them at very early stages might reduce creativity since they do not allow to superpose several tentative designs nor to refine them progressively, as sketches do. To enable exploratory design in 3D, we introduce Nested Explorative Maps, a new system dedicated to interactive design in architecture. Our model enables coarse to fine sketching of nested architectural structures, enabling to progressively sketch a 3D building from floor plan to interior design, thanks to a series of nested maps able to spread in 3D. Each map allows the visual representation of uncertainty as well as the interactive exploration of the alternative, tentative options. We validate the model through a user study conducted with professional architects, enabling us to highlight the potential of Nested Explorative Maps for conceptual design in architecture.